2007
DOI: 10.1161/01.hyp.0000254480.64564.b6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and Incidence of Hypertension Among Men Without Metabolic Syndrome

Abstract: Abstract-The aim of this project was to study the risk of developing hypertension over a 6-year follow-up in normotensive men with baseline hyperuricemia (serum uric acid Ͼ7.0 mg/dL) but without diabetes/glucose intolerance or metabolic syndrome. We analyzed the data on men without metabolic syndrome or hypertension at baseline from the Multiple Risk Factor Intervention Trial. These men (nϭ3073; age: 35 to 57 years) were followed for an average of 6 years by annual examinations. Follow-up blood pressure among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
170
0
12

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(188 citation statements)
references
References 38 publications
6
170
0
12
Order By: Relevance
“…In this 4-year follow-up study, we observed that elevated SUA levels were significantly and independently associated with the incidences of 10 In that study, subjects with hyperuricemia were at an 80% higher risk of developing hypertension, compared with those without hyperuricemia. The MRFIT study was a randomized, controlled trial in a cohort of men who were at high risk for adverse coronary events.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this 4-year follow-up study, we observed that elevated SUA levels were significantly and independently associated with the incidences of 10 In that study, subjects with hyperuricemia were at an 80% higher risk of developing hypertension, compared with those without hyperuricemia. The MRFIT study was a randomized, controlled trial in a cohort of men who were at high risk for adverse coronary events.…”
Section: Discussionmentioning
confidence: 71%
“…MetS is characterized by the presence of multiple common cardiovascular risk factors, such as central obesity, atherogenic dyslipidemia (hypertriglyceridemia and low high-density lipoprotein cholesterol (HDL-C)) levels, hyperglycemia and elevated blood pressure (BP). Elevated SUA levels are prevalent in patients with hypertension 1,2 and MetS, [3][4][5][6][7] and these levels can be a significant predictor of the development of hypertension 3,[8][9][10] and MetS. [11][12][13][14] Although evidence has suggested that elevated SUA levels might have a role in hypertension, 15 a causal relationship has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…12 A study found that men with hyperuricemia had more risk for incident hypertension. 13 Each unit increase in SUA was associated with a 9% increase in the risk for incident hypertension. Although the mechanism by which uric acid has a pathogenetic role in hypertension was unclear; hyperuricemia was associated with deleterious effects on endothelial function, platelet adhesion and aggregation, or oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…4 Therefore, we constructed the prediction models for hypertension risk using a community-based cohort of middle-aged and elderly ethnic Chinese in Taiwan as the following strategies. First, we incorporated gender, age, body mass index (BMI), systolic (SBP) and diastolic blood pressures (DBP) as the clinical model and included white blood cell count, fasting glucose and uric acid [12][13] as the biochemical models. Second, we proposed two different scoring systems: regression coefficient-based scores 14 and point-based scores.…”
Section: Introductionmentioning
confidence: 99%